2002
DOI: 10.13031/2013.9943
|View full text |Cite
|
Sign up to set email alerts
|

Concentration and Emissions of Ammonia and Particulate Matter in Tunnel–ventilated Broiler Houses Under Summer Conditions in Texas

Abstract: Total suspended particulate (TSP) concentrations, ammonia (NH 3) concentrations, and ventilation rates were measured in four commercial, tunnel-ventilated broiler houses in June through December of 2000 in Brazos County, Texas. TSP and NH 3 concentrations ranged from 7,387 to 11,387 mg m-3 and 2.02 to 45 ppm, respectively. Ammonia concentration exhibited a correlation with the age of the birds. Mass median diameters (MMD) of the TSP samples were between 24.0 and 26.7 mm aerodynamic equivalent diameter. MMD inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
39
1
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(50 citation statements)
references
References 4 publications
9
39
1
1
Order By: Relevance
“…A study developed in Texas [23] reported concentrations for PM10 ranging from 0.1 to 0.3 mg/m 3 . Our results showed higher concentrations in particles of these sizes probably due to the lower ventilation rates detected in our poultry facilities.…”
Section: Discussionmentioning
confidence: 99%
“…A study developed in Texas [23] reported concentrations for PM10 ranging from 0.1 to 0.3 mg/m 3 . Our results showed higher concentrations in particles of these sizes probably due to the lower ventilation rates detected in our poultry facilities.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the ventilation systems have direct effects on the spatial dust concentration whereas the increase of the ventilation rate will not necessarily reduce the overall dust level effectivel because the dust production rate will increase with increasing ventilation (Pedersen et al 2000). A comparative study of respirable dust concentration between European countries and the state of Texas in the USA has been presented by Redwine et al (2002). The dust Air Quality -New Perspective 292 concentration in European countries ranges in the literature from 0.4 to 9.7 mg.m -3 , on the other side, it ranges from 0.1 to 0.3 mg.m -3 in Texas, which is slightly less than comparable data from European studies.…”
Section: Indoor Dust Concentration and Emission Rate In Livestock Buimentioning
confidence: 99%
“…Bird age has a positive relationship with PM concentrations and emissions rates (Redwine et al, 2002). Hinz and Linke (1998b) determined PM concentrations increased linearly with broilers live weight.…”
Section: Factors Affecting Pm Generation and Levelsmentioning
confidence: 96%
“…Because of higher ventilation rates in summer compared with winter, low PM concentrations and high emission rates can be expected in the summer, whereas high PM concentrations and low emission rates can be expected in winter (Hinz and Linke, 1998b;Redwine et al, 2002). In a layer house, total and respirable PM formation rates were higher during hot weather ventilation rates, than during cold weather ventilation rates for total and respirable PM, because of an increased turbulence and suspension of PM .…”
Section: Factors Affecting Pm Generation and Levelsmentioning
confidence: 99%
See 1 more Smart Citation